Regular Exercise Training Enhances Spatial Memory and Regulates Glucocorticoid System in Experimental Autoimmune Encephalomyelitis - Muthanna Hafedh; Abdolhossein Parnow; Cyrus Jalili; Drapan Patel; Ikuo Tsunoda (Journal of Advanced Biomedical Sciences, 2021)
Background & objective: Exercise has been shown to improve cognitive function in patients with multiple sclerosis (MS). Experimentally, glucocorticoids (GCs) treatment has been observed to improve cognitive deterioration in an autoimmune model for MS, experimental autoimmune encephalomyelitis (EAE). We aimed to determine the combined effect of exercise and 4 mg/kg of dexamethasone (Dex) for 4 weeks on spatial memory in EAE. Materials & Methods: Rats with EAE were subjected to the Morris water maze (MWM) for four days and a prop test for one day. The prop test was repeated on day 40 post-induction (dpi). Rats were randomly assigned to one of four groups (10 rats per group): control EAE without treatment; EAE + dexamethasone, (EAE + Dex); EAE + exercise (EAE + Ex); and EAE+Dex+Ex. Rats receiving dexamethasone were administered 4 mg/kg injections daily for two weeks after EAE induction. Exercise training was initiated on a motorized treadmill 2 weeks before EAE induction and continued until 14 dpi. On day 41, animals were dissected and CORT level was assessed by enzyme-linked immunosorbent assay corticosterone kit. Results: One-way analysis of variance (ANOVA) with repeated measures followed by a protected LSD post hoc test indicated that, EAE+Ex group increased body weight (P < 0.001) and it displayed a significantly lower CORT concentration (P <0.001) with delayed clinical score until day 13 dpi. Further EAE+Ex improved memory by time spent (p > 0.001) and swimming speed (p>0.002). Conclusion: The protocol selected in this study was an effective treatment for the EAE model to improve spatial memory and regulate corticosterone concentrations.